Characterization of Opuntia ficus-indica (L.) Mill. fruit volatiles and antibacterial evaluation - Karadağ, Ayşe Esra; Demirci, Betül; Polat, Derya Çiçek; Okur, Mehmet Evren (Badebio Biotechnololgy Ltd, 2018)
Opuntia ficus-indica (L.) Mill. fruits known as prickly pear cactus are used in folk medicine as well as food. In the present study it was aimed to extract the volatile constituents of O. ficus-indica fruits by n-hexane. The volatiles were subsequently analyzed by GC-FID and GC-MS, where a total of 14 compounds were identified. The main components were characterized as hexadecanoic acid 39.4%, heptacosane 12.3%, and methyl linoleate 6.8%, respectively. Further antimicrobial evaulation using a broth microdilution assay (Clinical and Laboratory Standards Institute method) against human pathogenic Staphylococcus aureus ATCC 6538, Enterococcus faecalis ATCC 29212, Escherichia coli NRLL B-3008, and Pseudomonas aeruginosa ATCC 10145. The minimum non-reproductive concentrations were determined as MIC, where S. aureus showed the most potent inhibition by 500 µg/mL.
Keywords: Cactaceae; Chemical Characterization; Opuntia Ficus-İndica; Volatile Compounds